PENERAPAN MODEL COOPERATIVE LEARNING TIPE NUMBER HEADS TOGETHER UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS V SEKOLAH DASAR - Mariah Ulfah (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2016)
Aplication of Cooperative Learning Model of Number Heads Together(NHT) Type for Improved Mathematical Problem Solving in Fifth Grade. Thisresearch aims to: (1) describe the implementation of learning mathematics withapplication of cooperative learning model of NHT type in improving problem-solving abilities of fifth grade students at SDN Perumnas 02; and (2) describe the mathematical problem solving abilities increase abilities of fifth grade students at SDN Perumnas 02 with the implementation of cooperative learning model of NHT type in learning Mathematics. The method used is classroom action research Kemmis and Mc. Taggart models conducted in two cycles with qualitative and quantitative research approaches. Results from this study are: (1) the implementation of learning mathematics with application of cooperative learning model of NHT type of cycle I to cycle II of fifth grade students at SDN Perumnas 02, the better. Headband as numbering media to motivate students to learn. Giving the problem at this stage of questioning which is designed in the form of worksheets and given to each student develop a sense of personal responsibility so that when heads together students discuss with the group in solving problems. External motivation given teacher support internal motivation is able to create and enable the whole group to discuss; and (2) Application of cooperative learning model of NHT type can improve mathematical problem-solving abilities. Penerapan Model Cooperative Learning Tipe Number Heads Togetheruntuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa Kelas V Sekolah Dasar. Penelitian ini bertujuan untuk: (1) mendeskripsikan pelaksanaan pembelajaran matematika dengan menerapkan model Cooperative Learning Tipe NHT dalam meningkatkan kemampuan pemecahan masalah di kelas V SDN Perumnas 02; dan (2) mendeskripsikan peningkatan kemampuan pemecahan masalah matematis siswa kelas V di SDN Perumnas 02 dengan penerapan model Cooperative Learning Tipe NHT dalam pembelajaran Matematika. Metode yang digunakan yaitu penelitian tindakan kelas model Kemmis dan Mc Taggart yang dilaksanakan dalam dua siklus. Hasil dari penelitian ini yaitu: (1) pelaksanaan pembelajaran matematika dengan menerapkan model Cooperative Learning Tipe NHT dari siklus I ke siklus II di kelas V SDN Perumnas 02 semakin baik. Ikat kepala sebagai media numbering mampu memotivasi siswa untuk belajar. Pemberian masalah pada tahap questioning yang dirancang dalam bentuk LKS dan diberikan pada setiap siswa menumbuhkan rasa tanggung jawab pribadi sehingga pada saat heads together siswa berdiskusi dengan kelompoknya dalam memecahkan masalah. Motivasi eksternal yang diberikan guru mendukung motivasi internal yang mampu menciptakan dan mengaktifkan seluruh anggota kelompok untuk berdiskusi; dan (2) Penerapan model Cooperative Learning Tipe NHT dapat meningkatkan kemampuan pemecahan masalah matematis siswa.